Effects of an Elevated Platform on Welfare Aspects in Male Conventional Broilers and Dual-Purpose Chickens - Malchow, Julia; Schrader, Lars (Frontiers in Veterinary Science, 2021)
To avoid killing male day-old chicks, one possibility is to keep dual-purpose chicken strains. Here, the hens were kept for egg production, and the roosters were kept for meat production. Both sexes had moderate performances compared to the respective hybrid chicken strains. However, until now, little has been known about whether male dual-purpose chickens may profit from enrichment in the environment in which broiler chickens are raised under conventional conditions. This study aims to further investigate the suitability of elevated structures for dual-purpose chickens (Lohmann Dual) with moderate growth and for fast-growing male broiler chickens (Ross 308). In two consecutive trials, we kept 686 Ross and 672 Dual chickens in 24 compartments (2 trials x 2 strains x 6 compartments). Half of the compartments were equipped with elevated grid platforms at a height of 50 cm (enriched group). In the other half of the compartments, no platforms were installed (control group). We analyzed the usage of the elevated platforms by scan sampling and assessed animal-based (walking ability, plumage cleanliness, and foot health) and management-based (litter quality) indicators. Both strains showed increasing use of the elevated platforms from the first week of life onwards. However, the fast-growing chickens used the elevated platform less than the slow-growing chickens. At the end of the fattening period, the birds used the elevated grids more at night than during the daytime. Slow-growing chickens kept in enriched compartments showed a better walking ability. In general, slow-growing chickens had better plumage conditions and foot health compared to fast-growing chickens. Our results show that natural behaviors such as perching can be supported by offering elevated platforms and that animal-based indicators such as walking ability can be improved, at least in slow-growing chickens. Moreover, the use of an alternative chicken strain avoids killing male day-old chicks, and in addition, these chickens show fewer animal welfare problems than a conventional fattening strain. Thus, the use of male chickens of a dual-purpose strain can substantially contribute to improving animal welfare in broiler meat production.